THE LEVEL OF FARMERS' KNOWLEDGE OF DIGITAL MARKETING IN THE PEATLAND-CARING VILLAGE OF KUBU RAYA REGENCY - Aliyah Rahmanita; Erlinda Yurisinthae; Maswadi Maswadi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
The current state of agriculture has entered the era of digitalization, requiring farmers to understand digital technology, particularly in the field of agricultural product marketing. This aligns with one of the objectives of the Peat Care Village program, namely strengthening the economic support capacity of the peatland ecosystem. The purpose of this study is to analyze farmers’ level of knowledge and identify the factors influencing their knowledge of digital marketing in the Peat Care Village, Teluk Pakedai District, Kubu Raya Regency. The research method employed is descriptive quantitative analysis. The findings reveal that farmers in the Peat Care Village, Teluk Pakedai District, possess a level of knowledge categorized as “understanding.” The influencing factors include age and farming experience. Younger farmers are more receptive to new information, while farming experience affects the adoption of technological innovations. Therefore, it is necessary to enhance farmers’ knowledge through awareness programs, training, and the implementation of digital marketing practices.